Understanding health: a starting point in the healing focus when promoting health among young adult women (2010)
Via an intervention study with a before and after design, we worked with a group of 100 women between 20 and 40 years who are residents of the area of the Fourth regional district of the Capital, i.e. Bogotá (San Cristóbal, specifically), with the purpose of identifying the understanding of health before and after an intervention when promoting health drives with a healing focus, and the transformation that is generated after such intervention. In order to explore the concept of health and the actions needed to preserve health before and after, we used the semi-structured interview instrument, as of the judgments issued by women. We identified criteria and defined categories in order to understand the health concept and its evolution. At the beginning of the intervention, half the women understood health in terms of the absence of illnesses; one fifth associated it with corporal care, psycho spiritual and environmental care and one third integrated complex elements close to the category comprehension of healing in ones health. After the interventions the majority of the judgments issued by participants included criteria in this latter category. As a conclusion it is shown that the intervention strategy of promoting health with a healing focus to adult young women favors self thinking and the evolution of health conception, towards the recognition by women of their definitive role in being healthy and in the need for social contributions to a life project.